Detection of thermal pollution of urban reservoirs using the method of IR-radiometry based on the example of the Lake Kenon, Zabaykalsky Krai - Gurulev, Alexander A.; Kazantsev, Vyacheslav A. (Nexo Revista Científica, 2022)
Water bodies (e.g., rivers, lakes, and reservoirs) are an integral part of the urban environment. The infrastructure of the city affects their condition, in particular, pollution, including heat, which can lead to an increase in phyto- and zooplankton, including blue-green algae, and the appearance of toxins in the water. Identification of places where warm water is discharged into reservoirs is an urgent task. One of the methods of solving this problem is the monitoring of reservoirs from space. Thus, with the help of infrared satellite images, thermal anomalies are visible. In the work, we studied Lake Kenon located in the city of Chita. The satellite images were obtained from the Lansat-8. The channels used were 10 and 11, with a resolution of 60 meters. We revealed that (1) the optimal time for detecting thermal anomalies is the time before freezing in calm weather; (2) the cause of the thermal anomaly of this reservoir is a thermal power plant; (3) analysis of the last 5 years has shown that the water area with an increased surface temperature of the reservoir does not change; (4) the temperature gradient between cold and warm areas is 5°C; (5) the area of the heat spot does not exceed 10% of the total area of the lake. The above conclusions were confirmed using field measurements.